Eksistensi Hukum Internasional terhadap Hukum Nasional dalam Pembuatan Perjanjian Internasional - Laitupa, Salma; Dewi Kartika, Eka; Yasser Arafat J., Fadly (Amsir Law Journal, 2022)
The existence of international law has been accepted, recognized and respected as a legal norm that governs the international community. The rules of international law can be accepted and adapted in the national law of countries. The mechanisms and procedures used by each country to apply international law at the national level are not uniform. One of the main reasons is because they consider this a part of state sovereignty. As a system of norms, international law is based on the highest norms that function as an assessor of the validity of international agreements made between countries. The highest norms in international law are called peremptory norms (jus cogens). Therefore, an international agreement cannot be valid when an international agreement conflicts with the highest norms in international law